PLATO’S ETHICAL PHILOSOPHY AND RELEVANCE TO THE CONCEPT OF BIRR AL-WĀLIDAYN IN THE QUR’AN - Muhammad Zulfikar Nur Falah; Azzam Musoffa (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2023)
In Islam, a child is commanded to do good to his parents. Doing good is not only limited to outward attitudes but also to all aspects of attitude, words and deeds—including the inner aspect. This study talks about the relevance of Plato’s ethical philosophy to the concept of filial piety in the Qur’an. The background of the research points to the relationship between parents and children as fundamental in consciously shaping virtuous character. The relationship between teachers and students is like the relationship between children and their parents. Therefore, it is important to apply the attitudes of children towards their parents in the context of the relationship between teachers and their students. This research method uses descriptive analysis obtained through library research, which is obtained through relevant sources, such as books, journals, theses, dissertations, etc. The purpose of this study is of course to find out the relevance between Plato’s ethical philosophy and the concept of birr al-wālidayn in the Qur’an. Therefore, before moving on to discussing the relevance of Plato’s ethical philosophy to the concept of birr al-wālidayn in the Qur’an, the author first explains the meaning and classification of ethics, as well as ethical philosophy in Plato’s thought. The results of this research indicate that Plato’s ethical philosophy and the concept of birr al-wālidayn in the Qur’an, are relevant when denying the bad values that are often entrenched. It lies in the realization of ethical action, as stated only based on the value of goodness alone.